Enhancing transglutaminase production of Streptomyces mobaraensis by iterative mutagenesis breeding with atmospheric and room-temperature plasma (ARTP) - Jiang, Ying (Bioresour Bioprocess, 2017)
OBJECTIVES: To improve the fermentation production of transglutaminase (TGase) from Streptomyces mobaraensis for applications in the food industry, the atmospheric and room-temperature plasma (ARTP) mutagenesis was applied to breed S. mobaraensis mutants with increased TGase production. RESULTS: After eight rounds of iterative ARTP mutagenesis, four genetically stable mutants, Sm5-V1, Sm6-V13, Sm2-V10, and Sm7-V12, were identified, which showed increased TGase production by 27, 24, 24, and 19%, respectively. The best mutant Sm5-V1 exhibited a maximum TGase activity of 5.85 U/mL during flask fermentation. Compared to the wild-type strain, the transcription levels of the zymogen TGase genes in the mutants increased significantly as indicated by quantitative real-time PCR, while the gene nucleotide sequences of the mutants did not change at all. It was shown that the overexpression of TGase zymogen gene in the mutants contributes to the increase in TGase production. CONCLUSIONS: ARTP is a potentially efficient tool for microbial mutation breeding to bring some significant changes required for the industrial applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40643-017-0168-2) contains supplementary material, which is available to authorized users.